A study of the impact of technological innovation in food production on the resilience of the food industry - Wei Wang; Zhuoying Fu; Chongxu Liu; Jinghan Ding; Jiaxi Zheng; Chongmei Zhang; Haiyu Li (Journal of Innovation & Knowledge (JIK), 2025)
Based on the provincial panel data of 31 provinces in China from 2003 to 2022, this study constructed an evaluation system for the resilience of the food industry. We used the ordinary least squares model to empirically analyse the impact of technological innovation in food production on the resilience of the food industry. Furthermore, we applied the spatial Durbin model with spatiotemporal double fixed effects to investigate the potential spatial spillover effects of technological innovation in food production on industry resilience. The results indicate the following key points: (1) Technological innovation in food production has a positive influence on the resilience of the food industry, as well as on its risk resistance, adjustment and recovery and sustainability. However, this long-term impact exhibits a distinctly diminishing marginal character. (2) Technological innovations in food production increase the resilience of the food industry by optimising the employment structure. (3) Digital inclusive finance and its associated credit and payment services can enhance the positive impact of technological innovation in food production on the resilience of the food industry. Notably, digital inclusive finance is characterised by significant gradient differences and diminishing margins. (4) Technological innovation has a significant siphoning effect on the resilience of the food industry in neighbouring provinces. (5) Analyses of heterogeneity indicate that technological innovation has a significant siphoning effect on the resilience of the food industry in neighbouring provinces in the eastern, central and western regions. Meanwhile, a significant spillover effect is evident in the north-eastern region. This study's main contribution is providing empirical evidence to inform regionally differentiated policies aimed at improving the level of agrotechnological innovation and the resilience of the food industry.
Keywords: O31; O33; O38; Q16; 650; Food industry resilience; Spatial Durbin model; Spatial spillovers; Technological innovation